Dressings and dignity in community nursing. (2nd November 2021) - Stevens, Emma; Price, Elizabeth; Walker, Liz
Abstract : Although dignity has been widely explored in the context of healthcare, it has rarely been the subject of empirical exploration when care is delivered by community district nursing teams. This paper demonstrates how a commonplace community nursing task (changing dressings) can constitute a clinical lens through which to explore the ways in which community nurses can influence patients' dignity. This ethnographic study involved two research methods: interviews with patients and nurses (n=22) and observations of clinical interactions (n=62). Dignity can manifest during routine interactions between community nurses and patients. Patient-participants identified malodour from their ill-bodies as a particular threat to dignity. Nurses can reinforce the dignity of their patients through relational aspects of care and the successful concealment of 'leaky' bodies.